REALISMO EN TIEMPOS DE IRREALIDAD. (EL NUEVO REALISMO ESPAÑOL A LA LUZ DE LA POSTMODERNIDAD) - Cruz Sánchez, Pedro A. (Imafronte, 1999)
New Spanish Realism. in spite of being an emerging artistic movement hoth quantitatively and qualitatively, has as yet not received full recognition from the critics. In this paper the intention is to examine the specific characteristics of this artistic tendency in the context of postmodernist tought, demonstrating that this new realism provides an interesting answer to prevalent comtemporary cultural and philosophical schemes. This relationship between the News Realism and Posmodernity will he analysed from three points of view: the lightening of reality, cultures as the framework of reality and the fragmentation of the word of phenomena.